2020
DOI: 10.5114/amsad.2020.95651
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of carotid intima media thickness by B-mode ultrasonography in coronary artery disease patients

Abstract: Introduction: Cardiovascular diseases (CVD) are the main cause of premature deaths worldwide, and atherosclerosis (AS) is a major risk factor associated with them. B-mode ultrasound is a well-validated research tool that has been translated increasingly into clinical practice. The aim of the study was to assess the diagnostic accuracy of carotid intima media thickness by B-mode ultrasonography in coronary artery disease patients. Material and methods: This was a case control study, including 100 cases and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Yet, the DUS is a safe, easy, and cost-effective screening investigative tool that can be routinely employed in the clinic [ 105 , 106 ], and has a sensitivity and specificity of 90% and 94% for carotid artherosclerosis [ 107 ]. Additionally, the DUS can double as a screening modality for coronary artery disease (CAD) with a respective sensitivity and specificity of 78% and 75% for CAD [ 108 ]. CAD is a known complication of NAFLD, and recent estimates suggest the prevalence of CAD to be 38.7% and 55.4%, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the DUS is a safe, easy, and cost-effective screening investigative tool that can be routinely employed in the clinic [ 105 , 106 ], and has a sensitivity and specificity of 90% and 94% for carotid artherosclerosis [ 107 ]. Additionally, the DUS can double as a screening modality for coronary artery disease (CAD) with a respective sensitivity and specificity of 78% and 75% for CAD [ 108 ]. CAD is a known complication of NAFLD, and recent estimates suggest the prevalence of CAD to be 38.7% and 55.4%, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size and dynamics of IMT can help in determining optimal therapeutic interventions as well as in the application of other diagnostic tools; see [12]. Although there are studies that have presented a discrepancy between carotid IMT changes, prognosis, and the course of cardiovascular pathologies [13,14], the overwhelming clinical data (see [15][16][17][18][19]) strongly confirm that the IMT will continue to be used as a valuable tool in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Markers of subclinical atherosclerosis should be considered in high-risk individuals, such as computed tomography scanning to assess CAC, or carotid IMT and carotid atherosclerotic plaques. Assessment of carotid artery ultrasound is a widely used, reliable and cost-effective screening tool that can be routinely employed in the clinic with incremental prognostic value over traditional CVD risk factors in patients with MAFLD, who are typically asymptomatic [ 100 ]. A recent meta-analysis suggested that the pooled prevalence of subclinical and clinical CVD in NAFLD was 38.7% and 55.4%, respectively.…”
Section: Consensus Statements and Recommendationsmentioning
confidence: 99%